2014
DOI: 10.1128/aem.01249-14
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Self-Assembling Amphipathic Oligopeptides with Cyclodextrin Glycosyltransferase Improves 2- O - d -Glucopyranosyl- l -Ascorbic Acid Synthesis with Soluble Starch as the Glycosyl Donor

Abstract: In this study, we fused six self-assembling amphipathic peptides (SAPs) with cyclodextrin glycosyltransferase (CGTase) from Paenibacillus macerans to catalyze 2-O-D-glucopyranosyl-L-ascorbic acid (AA-2G) production with cheap substrates, including maltose, maltodextrin, and soluble starch as glycosyl donors. The results showed that two fusion enzymes, SAP5-CGTase and SAP6-CGTase, increased AA-2G yields to 2.33-and 3.36-fold that of wild-type CGTase when soluble starch was used as a substrate. The cyclization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…To replace cyclodextrin with a less expensive and in terms of glucosyl content more completely utilizable donor substrate (e.g., starch, maltodextrin, or maltose), other CGTases in native or engineered form were considered. Variants of P. macerans CGTase showed enhanced specificity toward these noncyclic substrates. However, the AA-2G yields thus obtained were still much lower than the “benchmark” yield using cyclodextrin. ,,, Interestingly, the increased disproportionation activity of the CGTase variants proved to be beneficial for the yield of AA-2G from cyclodextrin. ,, However, the engineered CGTases often showed a substantially lowered efficiency in the reaction with l -AA as compared to that with the wild-type enzyme. Table indicates strong variation in the degree of utilization of l -AA in the different studies of AA-2G synthesis performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To replace cyclodextrin with a less expensive and in terms of glucosyl content more completely utilizable donor substrate (e.g., starch, maltodextrin, or maltose), other CGTases in native or engineered form were considered. Variants of P. macerans CGTase showed enhanced specificity toward these noncyclic substrates. However, the AA-2G yields thus obtained were still much lower than the “benchmark” yield using cyclodextrin. ,,, Interestingly, the increased disproportionation activity of the CGTase variants proved to be beneficial for the yield of AA-2G from cyclodextrin. ,, However, the engineered CGTases often showed a substantially lowered efficiency in the reaction with l -AA as compared to that with the wild-type enzyme. Table indicates strong variation in the degree of utilization of l -AA in the different studies of AA-2G synthesis performed.…”
Section: Resultsmentioning
confidence: 99%
“…30,32,48,49 Interestingly, the increased disproportionation activity of the CGTase variants proved to be beneficial for the yield of AA-2G from cyclodextrin. 32,50,51 However, the engineered CGTases often showed a substantially lowered efficiency in the reaction with L-AA as compared to that with the wild-type enzyme. Table 1 indicates strong variation in the degree of utilization of L-AA in the different studies of AA-2G synthesis performed.…”
Section: Acs Catalysismentioning
confidence: 99%
“…[ 10 ] The strategies including engineering CGTase and creating the fusion enzyme have effectively improved the specificity towards maltose or soluble starch, which are cheap and can be easily dissolved in aqueous solution. [ 47,48 ] Sucrose phosphorylase is another candidate enzyme that catalyzes the formation of AA‐2G from sucrose and L‐AA, but the existence of by‐product 6‐ O ‐ α ‐glucopyranosyl‐L‐ascorbic acid inevitably increased difficulty of AA‐2G purification. [ 17 ] At low pH value of 5.2, the sucrose phosphorylase from B. longum was proved to be both efficient and site‐selective for AA‐2G synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that maltodextrin specificity is enhanced by site-saturation engineering of lysine 47 [ 46 ], tyrosine 195, tyrosine 260, and glutamine 265 [ 48 ], or the iterative saturation mutagenesis of -6 sub site residues [ 47 ] in α-CGTase extracted from Paenibacillus macerans when used to synthesize 2-O-D-glucopyranosyl-L-ascorbic acid. Moreover, starch specificity can be enhanced by chimeric modification, including fusion of the carbohydrate-binding module to the carboxyl terminus of CGTase, fusion of self-assembling amphipathic oligopeptides with α-CGTase [ 45 ], or replacing the E domain of α-CGTase [ 43 ], to synthesize 2-O-D-glucopyranosyl-L-ascorbic acid. The donor's specificity improvement makes the glycosyl donors more soluble and the synthesis of 2-O-D-glucopyranosyl-L-ascorbic acid cheaper [ 44 ].…”
Section: Strategies To Improve the Transglycosylation Activity Of Cgtmentioning
confidence: 99%